Antenatal and Post-natal Check-up Practices Among Chepang and Non-Chepang Communities of Nepal - Ghimire, Mayanath; Maharjan, Ram Krishna (Journal of Advanced Academic Research, 2017)
Health check-up during pregnancy and after pregnancy is a must because of the critical health status of the mother and baby. The study identifies the health seeking behavior of mothers of Chepang and Non-Chepang communities of Makawanpur and Chitwan district of Nepal regarding the ANC and PNC check-up. The study was cross sectional descriptive design. Total sample size was 1250 (511 Non-Chepang and 739 Chepang). The result found that Non-Chepang community was found more aware and better practice of health check-up than Chepang communities in both districts. Nepal Government should focus on Chepang or similar types of marginalized and backward communities to increase their access on health services as well as concerned authorities should be responsible to address their problem which become as barrier to change their health seeking behavior.